UNJUK KERJA SISTEM OFDM DENGAN MENGGUNAKAN ALGORITMA VFFT PADA KANAL AWGN - N.K.W. Trisnawati; N.M.A.E.D. Wirastuti; I.G.A.K.D.D. Hartawan (Jurnal SPEKTRUM, 2022)
The computational load and implementation costs of a system are affected by its complexity. The Fast Fourier Transform(FFT).algorithm use in an OFDM system necessitates intensive calculations, which affects the computational load and system complexity. There is a Very Fast Fourier Transform(VFFT) algorithm which has lower complexity than the FFT, and can replace FFT with Floating-Point accuracy. The aim of this study is to determine the performance of the OFDM system by using the FFT and VFFT algorithms over the AWGN channel, based on parameter value of BER vs. Eb/No. According to the simulation results, show that the OFDM (FFT) system has a better BER value, where when Eb/No reaches 6 dB the BER value is less than 10-2, while the OFDM(VFFT) system with a BER value is 10-2, but still has almost the same trend. This is because there is non uniform row gain in the OFDM(VFFT) system. However, with this weakness, OFDM(VFFT) can minimize the complexity of the OFDM system.